Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.

Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Efficient gamma-Fe2O3 catalyst for liquid phase air oxidation of p-hydroxybenzyl alcohol under mild conditions - Garade, Ajit C.; Bharadwaj, M.; Bhagwat, S. V.; Athawale, A. A.; Rode, C. V. (Catalysis Communications, 2009)
gamma-Fe2O3 (maghemite) particles were synthesized at 5 degrees C (LT, low temperature) and 95 degrees C (HT, high temperature) using a simple chemical protocol. The major reflection in XRD was observed to be of the gamma-Fe2O3 phase which was further supported by the XPS analysis. Fe3+ species were responsible for initiation of the oxidation of p-hydroxybenzyl alcohol. SEM revealed that the morphologies of the catalysts were different for samples prepared at two different temperatures. gamma-Fe2O3 (LT) showed the highest catalyst activity (84% conversion) for liquid phase air oxidation of p-hydroxybenzyl alcohol with 94% selectivity to the oxidation products at 370 K and ambient pressure conditions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Air oxidation; gamma-Fe2O3; p-Hydroxybenzaldehyde; p-Hydroxybenzyl alcohol; scanning electron microscopy

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol

Effect of SnO2/Al2O3 ratio of Si-based MFI on its acidity and hydrophobicity: application in selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Malwadkar, A. V.; Niphadkar, P. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Rode, C. V. (Catalysis Communications, 2014)
Silica based MR type molecular sieves with various SnO2/Al2O3 ratios were synthesized from gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23(TPA)(2)O:35H(2)O where 0 <= x <= 0.02 and 0 <= y <= 0.01. Recyclable, Al-free Sn-MFI catalyst showed 31% conversion of formaldehyde with 100% selectivity to 2,2'-methylenebis(4-methylphenol) in hydroxyalkylation of p-cresol with formaldehyde on account of moderate acidity and higher hydrophobicity. (C) 2013 Elsevier B.A. All rights reserved.
Keywords: Al-27 MAS NMR; Hydroxyalkylation; Molecular sieves; p-Cresol; Stannosilicate

Effect of reduction protocol of Pd catalysts on product distribution in furfural hydrogenation - Date, N. S.; Biradar, N. S.; Chikate, R. C.; Rode, C. V. (ChemistrySelect, 2017)
Single step conversion of furfural to ring hydrogenation and decarbonylation products, 2-methyltetrahydrofuran (2-MeTHF) and tetrahydrofuran (THF) in high selectivity was achieved by controlling the particle size of Pd/C catalyst. The particle size variation of Pd/C catalysts in the range of 3.8 to 22 nm could be achieved by employing different reducing agents. Of particular interest was the NaBH4 reduced catalyst (Pd-B/C), which gave the lowest crystallite size of 4.8 nm due to incorporation of B into the inner lattices of Pd-Pd. This phase was evidenced by a characteristic XRD peak of Pd-B at 2q=38.85 degrees as well as a shift of (111) peak (40.07 degrees) of Pd towards the lower value (39.8 degrees). As compared to formaldehyde reduced catalyst (Pd-F/C), Pd-B/C catalyst completely suppressed the formation of furfuryl alcohol to give > 65% selectivity to 2-MeTHF and THF. At 180 degrees C, almost equal distribution of side chain hydrogenation and ring opening products, 2-MF (45%) and PeDO (37 %), respectively, was observed while, higher temperature clearly favoured ring hydrogenation and decarbonylation reactions to give 2-MeTHF and THF.